Cognitive remediation therapy (CRT) as a treatment enhancer of eating disorders and obsessive compulsive disorders: study protocol for a randomized controlled trial. Issue 1 (December 2016) - van Passel, Boris; Danner, Unna; Dingemans, Alexandra; van Furth, Eric; Sternheim, Lot; van Elburg, Annemarie; van Minnen, Agnes; van den Hout, Marcel; Hendriks, Gert-Jan; Cath, Daniëlle
Abstract Background Anorexia nervosa (AN) and Obsessive Compulsive Disorder (OCD) are among the most incapacitating and costly of mental disorders. Cognitive Behaviour Therapy (CBT), medication, and combination regimens, to which in AN personalised guidance on weight control is added, are moderately successful, leaving room for more effective treatment algorithms. An underlying deficit which the two disorders share is cognitive inflexibility, a trait that is likely to impede treatment engagement and reduce patients' ability to benefit from treatment. Cognitive remediation therapy (CRT) is an easy-to-use intervention aimed at reducing cognitive inflexibility and thereby enhancing treatment outcome, which we aim to test in a controled study. Methods In a randomized-controlled multicenter clinical trial 64 adult patients with AN and 64 with OCD are randomized to 10 bi-weekly sessions with either CRT or a control condition, after which Treatment As Usual (TAU) is started. All patients are evaluated during single-blind assessments at baseline, post-CRT/control intervention, and after 6 months. Indices of treatment effect are disorder-specific symptom severity, quality of life, and cost-effectivity. Also, moderators and mediators of treatment effects will be studied. Discussion To our knowledge, this is the first randomized controlled trial using an control condition evaluating the efficacy and effectiveness of CRT as a treatment enhancer preceding TAU for AN, and the first study to investigate CRT in OCD, moreover taking cost-effectiveness of CRT in AN and OCD into account. Trial registration The Netherlands Trial RegisterNTR3865 . Registered 20 february 2013.